Evaluasi Kinerja Pegawai Berbasis Teknologi: Implementasi Sistem Pendukung Keputusan dengan Metode Profile Matching - Karya Suhada; Dede Hendrik; Andriyana Andriyana; Evi Isnandar; Yessy Yanitasari (Bulletin of Information Technology (BIT), 2025)
Employee performance evaluation is an important process to improve work efficiency and effectiveness in government agencies. At the Simpang Empat District Office, the performance evaluation process is still carried out manually, which is often time consuming and prone to subjectivity. This research aims to develop a Decision Support System (DSS) based on the Profile Matching method to assist the employee performance evaluation process. This research uses the Profile Matching method, where the ideal performance profile is used as a reference for assessing individual performance. Employee performance data is collected through work assessments, interviews and direct observation. The SPK system developed is designed to automate the evaluation process by comparing employee performance profiles with ideal performance profiles. This system succeeded in reducing evaluation time by up to 50% and increasing assessment accuracy compared to manual methods. Employees with substandard performance can be identified quickly, allowing for timely intervention.